2013
DOI: 10.1002/emmm.201201320
|View full text |Cite
|
Sign up to set email alerts
|

WNT10B/β‐catenin signalling induces HMGA2 and proliferation in metastatic triple‐negative breast cancer

Abstract: Wnt/β-catenin signalling has been suggested to be active in basal-like breast cancer. However, in highly aggressive metastatic triple-negative breast cancers (TNBC) the role of β-catenin and the underlying mechanism(s) for the aggressiveness of TNBC remain unknown. We illustrate that WNT10B induces transcriptionally active β-catenin in human TNBC and predicts survival-outcome of patients with both TNBC and basal-like tumours. We provide evidence that transgenic murine Wnt10b-driven tumours are devoid of ERα, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
163
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 47 publications
4
163
2
Order By: Relevance
“…Taken together, the strong reduction of ERBB2 expression observed upon ablation of b-catenin activity either through RNA interference or IGC-001 is due to a disruption of the ERRa/b-catenin/CBP-dependent recruitment of RNA polymerase II to an intronic ERBB2 site that regulates ERBB2 transcription. Consistent with these data, it has been previously shown that ICG-001 specifically interferes with the ability of b-catenin to form complexes with CBP and Lef1 (54). The ICG-001-dependent reduction in GRB7 transcription can also be attributed to the fact that the proximal promoters of GRB7 and other ERBB2 amplicon components are also regulated by these b-catenin-containing complexes ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Taken together, the strong reduction of ERBB2 expression observed upon ablation of b-catenin activity either through RNA interference or IGC-001 is due to a disruption of the ERRa/b-catenin/CBP-dependent recruitment of RNA polymerase II to an intronic ERBB2 site that regulates ERBB2 transcription. Consistent with these data, it has been previously shown that ICG-001 specifically interferes with the ability of b-catenin to form complexes with CBP and Lef1 (54). The ICG-001-dependent reduction in GRB7 transcription can also be attributed to the fact that the proximal promoters of GRB7 and other ERBB2 amplicon components are also regulated by these b-catenin-containing complexes ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 78%
“…2A) associated with decreased cyclin D1 expression, and increased G0/G1 phase population and reduced S phase population. Furthermore, c-Fos, as well as β-catenin, has previously been demonstrated to function as a nuclear transcription factor (23,24). In addition, in the present study, their expression was found to be decreased by caveolin 1 knockdown in BT474 cells (Fig.…”
supporting
confidence: 75%
“…For example, familial adenomatous polyposis (FAP) patients carry a mutated germline APC, which is unable to suppress b-catenin accumulation and promotes colorectal carcinomas (CRC) in the context of mutated KRAS and P53 [20,21]. Moreover, overexpression of WNT3A and WNT10B is positively associated with the development of breast cancers [22]. Mutations in the b-catenin gene, CTNNB1 are prevalent in many cancers such as those of hepatocellular, gastric, pancreas, ovarian and endometrial malignances [23].…”
Section: Wnt/b-catenin Signalling Pathway and Cancermentioning
confidence: 99%